Key for crossing the BBB with nanoparticles: the rational design - Lombardo, Sonia M; Schneider, Marc; Türeli, Akif E; Günday Türeli, Nazende (Beilstein journal of nanotechnology, 2020)
Central nervous system diseases are a heavy burden on society and health care systems. Hence, the delivery of drugs to the brain has gained more and more interest. The brain is protected by the blood–brain barrier (BBB), a selective barrier formed by the endothelial cells of the cerebral microvessels, which at the same time acts as a bottleneck for drug delivery by preventing the vast majority of drugs to reach the brain. To overcome this obstacle, drugs can be loaded inside nanoparticles that can carry the drug through the BBB. However, not all particles are able to cross the BBB and a multitude of factors needs to be taken into account when developing a carrier system for this purpose. Depending on the chosen pathway to cross the BBB, nanoparticle material, size and surface properties such as functionalization and charge should be tailored to fit the specific route of BBB crossing.